2016
DOI: 10.1021/acs.orglett.5b03676
|View full text |Cite
|
Sign up to set email alerts
|

Mallotojaponins B and C: Total Synthesis, Antiparasitic Evaluation, and Preliminary SAR Studies

Abstract: The first total syntheses of mallotojaponin B and C as well as several analogues have been achieved. Biological evaluation of the synthesized compounds against Plasmodium falciparum and Trypanosoma brucei have also been carried out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…Many monomeric phloroglucinols have been investigated for their antimalarial activity, 3 5 and some additional dimeric compounds from M. oppositifolius have recently been shown to have trypanocidal and antileishmanial activities. 6 This paper describes the syntheses and biological evaluations of mallotojaponin C and various derivatives that were reported in 2015 in a Ph.D. dissertation 7 and complements the results in an excellent recent paper by Cariou and Dubois et al 8 …”
supporting
confidence: 70%
See 2 more Smart Citations
“…Many monomeric phloroglucinols have been investigated for their antimalarial activity, 3 5 and some additional dimeric compounds from M. oppositifolius have recently been shown to have trypanocidal and antileishmanial activities. 6 This paper describes the syntheses and biological evaluations of mallotojaponin C and various derivatives that were reported in 2015 in a Ph.D. dissertation 7 and complements the results in an excellent recent paper by Cariou and Dubois et al 8 …”
supporting
confidence: 70%
“… 9 , 10 The use of sodium hydroxide led to higher yields of 11 , 12 , 16 , and 17 than the use of lithium hydroxide. Compounds 11 , 8 , 11 − 14 16 , 14 17 17 , 18 , 19 and 18 ( 17 , 20 ) have previously been synthesized, and their structures were confirmed by MS and by comparison of their 1 H and 13 C NMR spectra with previously published spectra. Thus, treatment of 10 with 3,3-dimethylallyl bromide (prenyl bromide) in 80% aqueous ethanol with 1.1 equiv of NaOH at room temperature for 16 h gave the monoprenylated product 11 in 33% yield.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Grayfer et al 68 found that the modification of the prenylated side chain of the natural product can regulate biological activity. For example, an increase in the number of prenyl units on the side chain of mallotojaponin B may enhance anti-malarial and FTase inhibitory activity.…”
Section: Aplidium Conicummentioning
confidence: 99%
“…All three peptides inhibited chymotrypsin activity, with IC 50 values of 0.62, 2.8, and 2.3 nM, respectively, and elastase with IC 50 values of 34, 100, and 99 pM, respectively. 60)…”
Section: Phenolic Compounds Four Novel Diphenylpropanes Bussealines mentioning
confidence: 99%